2006
DOI: 10.1111/j.1600-6143.2006.01427.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Renal IschemiaReperfusion Injury Using Small Interfering RNA by Targeting Complement 3 Gene

Abstract: The complement system is one of the important mediators of renal ischemia-reperfusion injury (IRI). We hypothesized that efficient silencing of C3, which is the central component on which all complement activation pathways converge, could be achieved using small interfering RNA (siRNA), and that this would result in overall inhibition of complement activation, thereby preventing IRI in kidneys. A series of experiments was conducted, using a mouse model of IRI and vector-delivered C3-specific siRNA. We demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 41 publications
(55 reference statements)
2
51
0
Order By: Relevance
“…Kidneys can express massive amounts of complement, as in the case of rejecting allografts. 22 On the other hand, using a mouse I/R injury model, we have demonstrated that the renal expression or deposition of C9 occurs early after reperfusion and is localized to cellular debris and injured tubular epithelial cells, which is consistent with our previous study 7,9 and is supported by the view that the complement pathway is crucially involved in renal I/R injury. 16,[23][24][25] In our present study, we extend the link between renal I/R injury and complement by demonstrating that specific blockade of C5aR expression using siRNA can prevent renal I/R injury.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Kidneys can express massive amounts of complement, as in the case of rejecting allografts. 22 On the other hand, using a mouse I/R injury model, we have demonstrated that the renal expression or deposition of C9 occurs early after reperfusion and is localized to cellular debris and injured tubular epithelial cells, which is consistent with our previous study 7,9 and is supported by the view that the complement pathway is crucially involved in renal I/R injury. 16,[23][24][25] In our present study, we extend the link between renal I/R injury and complement by demonstrating that specific blockade of C5aR expression using siRNA can prevent renal I/R injury.…”
Section: Discussionsupporting
confidence: 84%
“…3,15,16 We previously showed that inhibiting C3 with siRNA protected renal from I/R injury. 7,9,10 In this study, we have demonstrated that silencing the C5aR gene using siRNA can inhibit the renal expression of C5aR and that successful delivery of C5aR-siRNA to the kidneys results in the prevention of renal I/R injury.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Morphological changes in the cor tex and medulla were scored in a blinded fashion by two pathologists according to the severity of tubular necrosis, integrity of brush border and basement membrane, and cast formation. The scoring included 4 scales: 0) <10%; 1) 10% to 25%; 2) 25% to 50%; 3) 50% to 75%; and 4) >75% (36). Each section was assessed with randomly selected 10 highpower fields (magnifica tion, × 400), and three mice were included in each study group.…”
Section: Introductionmentioning
confidence: 99%